Treatment of Rhinophyma With Surgical Excision and Amniotic Membrane. Issue 5 (July 2019) - Yoo, Jason J.; Thaller, Seth R.
Abstract : Abstract: Rhinophyma is a phenotypic subtype of rosacea affecting the nose. It is characterized by phymatous changes, skin thickening/fibrosis, glandular hyperplasia, and chronic inflammation. Treatment of severe rhinophyma is predominantly surgical excision with closure by secondary intention. Amniotic membrane has been used to promote wound healing, fibrosis, and inflammation. In this case study, the authors present a 63-year-old male with longstanding rhinophyma treated with surgical excision with intraoperative placement of amniotic membrane.